1997
DOI: 10.1029/97jd00456
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impact of averaging on aggregation of surface fluxes over BOREAS

Abstract: variability and intensity of surface and subsurface fluxes of heat and moisture and showed that they exerted a significant influence on mesoscale dynamics over the relatively small (15 x 15 km) FIFE study area.The problem of properly assimilating small-scale fluxes into large-scale models has also received considerable attention. In regional models, a single horizontal grid element can cover between 103 and 10 4 km 2, while in global climate models (GCMs), the grid size can be l0 s km 2, or larger. At these sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…3.3). Many studies exist, usually focused on the local scale, which have compared parameter aggregating to flux-aggregating techniques (see e.g., Avissar and Pielke 1989;Polcher et al 1996;Van den Hurk and Beljaars 1996;Cooper et al 1997;Molod and Salmun 2002;Essery et al 2003;Heinemann and Kerschgens 2005;Ament and Simmer 2006). These studies agree that by employing an aggregation of fluxes the representation of processes clearly improves compared to an aggregation of parameters.…”
Section: Introductionsupporting
confidence: 52%
“…3.3). Many studies exist, usually focused on the local scale, which have compared parameter aggregating to flux-aggregating techniques (see e.g., Avissar and Pielke 1989;Polcher et al 1996;Van den Hurk and Beljaars 1996;Cooper et al 1997;Molod and Salmun 2002;Essery et al 2003;Heinemann and Kerschgens 2005;Ament and Simmer 2006). These studies agree that by employing an aggregation of fluxes the representation of processes clearly improves compared to an aggregation of parameters.…”
Section: Introductionsupporting
confidence: 52%
“…A comparison of mosaic and mixture for a terrain type which is homogeneously covered by two vegetation types (savannah, where mixture is an accurate representation) was performed by Koster and Suarez [1992b], who showed that the resulting fluxes using the mosaic approach are quite close to the mixture results. Studies by Cooper et al [1997], van den Hurk and Beljaars [1996], Arola and Lettenmaier [1996], and Polcher et al [1996] all reported significant differences between mosaic and composite during the spring and summer at several different Northern Hemisphere locations. These studies find that the mosaic representation reduces the latent heat fluxes (and increases the sensible heat) and offers the more accurate estimates of surface fluxes.…”
Section: Introductionmentioning
confidence: 97%
“…Sampaio et al, 2007;da Silva et al, 2008), and modelling studies using the tile approach (e.g. Arola and Lettenmaier, 1996;Polcher et al, 1996;van den Hurk and Beljaars, 1996;Cooper et al, 1997). These differences indicate a reduction in evaporation and net radiation, and an increase in skin temperature, sensible heat flux, surface albedo, and near-surface winds.…”
Section: Discussionmentioning
confidence: 99%
“…These aggregation methods are widely used in landsurface modelling and have shown satisfactory results in the representation of surface processes (e.g. Arola and Lettenmaier, 1996;Polcher et al, 1996;van den Hurk and Beljaars, 1996;Cooper et al, 1997;Molod and Salmun, 2002;Manrique-Suñén et al, 2013).…”
Section: Introductionmentioning
confidence: 99%